All-Inside Anterior Cruciate Ligament Reconstruction With Augmentation Using the Native Anterior Cruciate Ligament Remnant by Suture Approximation - George El Rassi, M.D. (Arthroscopy Techniques, 2021)
Anterior cruciate ligament (ACL) rupture remains a debilitating orthopaedic pathology with a substantial economic and psychological burden on patients, especially athletes. The purpose of ACL reconstruction is to attain maximum joint stability and functionality, allowing patients to resume their previous level of activity. Several graft options and techniques are available for ACL reconstruction. The all-inside remnant-preservation technique is a minimally invasive approach aiming for improved proprioception, better graft integration, and increased graft strength via ACL augmentation by suture approximation with an optimal anatomic reconstruction. ACL augmentation is associated with a decreased risk of rerupture. Moreover, enhancement of knee proprioception via the presented technique allows an early return to activity by patients because weight bearing (with a brace) can be initiated as early as day 1 postoperatively. Patients can resume running activities by 2 months postoperatively and return to pivot sports by 3 months postoperatively. Despite this surgical procedure being technically demanding, it is associated with improved clinical outcomes and functional capacities. Patients are also found to better tolerate the postoperative rehabilitation protocol.